Making wine production “fair” through sports? An analysis of sports as an aspect of farm worker development in the Cape Winelands - Kaur, Tarminder (Acta Academica: Critical views on society, culture and politics, 2018)
Questioning the role of sports in making wine production “fair”, this paper interrogates the tension between wishful benefits from sports and the contradictions in the way sports were experienced in the everyday. I selected the Fairhills Association, a Fairtrade wine initiative based in Rawsonville, Western Cape, as my case study because of its sports programme for the affiliated farm workers. Given the infamous history of exploitative labour practices, the move to transform the South African wine industry into a more ethical operation has evidently meant development projects for the workforce. So, the sports activities were sponsored by the Fairhills Association with explicit development goals. Drawing on my ethnographic observations recorded at the sports fields in Rawsonville and interviews conducted on the history and contemporary practices of sports among the farm workers, I argue that: irrespective of the intended outcomes from the sports-for-development project, sports, unwittingly, becomes a conduit to express, mobilise and appropriate desires for a better life by those stuck in relatively compromised positions of power.